Perfil epidemiológico e psiquiátrico de crianças e adolescentes dependentes químicos hospitalizados no Brasil Central - Vilela, Ana Caroline Marques (2016)
Background: Adolescence is evidenced as one of the age groups the incidence of drug users is high and growing, and this finding suggests the study and research on a variety of questions about the possible relationship between these two phenomena. Attempts to characterize adolescent drug users and the various aspects of its use are of particular importance to contribute to the understanding of substance abuse patterns among young people, as well as provide data for guidance and prevention in the field of problems relating to drugs. Aim: Describe the epidemiology, identify the factors associated with drug use and the presence of dual pathology in adolescents hospitalized in the Midwest of Brazil. Methods: Cross-sectional study of adolescent (10-18 years) drug users hospitalized in Children's Mental Health Association of Goiás between 2010 and 2015. Data were collected retrospectively by chart review. Only patients with chemical dependence on licit or illicit substances as the reason for hospitalization were selected for data collection. Sociodemographic variables and sample characterization, drug usage profile, environmental factors and dual pathologies were collected in a standardized form. Descriptive analysis and association of drug use profile for sex by Chi-square test or Fisher's exact with an alpha of 5% was performed. Results: Among the 214 adolescents studied, 70.2% were male. An early onset of drug use was detected, with a mean age of 13 ± 2 years. Approximately 50% of patients dropped out of school due to drugs and were involved in illegal acts to obtain drugs. The cannabis was the psychoactive substance responsible for most admissions in males, while in females was crack (p = 0.031). Cannabis was the first drug used in life for most individuals, followed by tobacco and alcohol. The main dual pathologies were disruptive behavior disorders (50.0%) and mood disorders (46.7%). Conclusion: This study found a high prevalence of dual disorders, high dropout rates from school due to drug use, involvement in illicit activities to obtain drugs and early onset of substance abuse.